Challenges and Opportunities Towards Quality Education in Indonesia and Malaysia - Sulistiana, Tati; Imron, Ali (Proceedings Series of Educational Studies, 2024)
Quality education is considered an essential component for the progress of a nation. However, both countries face various obstacles, including the quality of teaching staff, infrastructure disparities, and differences in access to education between urban and rural areas. On the other hand, opportunities that exist through innovative policies, the application of technology in the learning process, and international collaboration can be utilized to improve the quality of education. This research applies a qualitative approach with literature analysis to assess educational policies and their impact on student learning outcomes. The findings show that although the challenges faced are significant, strategic steps can be taken to address these issues and improve the quality of education in both countries. By taking advantage of existing opportunities, it is hoped that Indonesia and Malaysia can build an education system that is more inclusive and relevant to global needs.